Agreement on Providing Working Capital Credit - Maesaroh Haris, Faradhilla Ayun; Abbas, Ilham; Zulkifli Muhdar, Muhammad (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study uses empirical legal research methods, empirical legal research is basically a combination of normative legal approaches with the addition of various empirical elements. In this empirical research method, it is also about the implementation of the legal provisions of the law in action in every particular legal research that occurs in society. The results of this study indicate that the procedure for granting Working Capital Credit (KMK) at PT. Bank Sulselbar Mamuju Branch is guided by the procedures and principles of providing sound credit and in accordance with applicable regulations. And the efforts made by Bank Sulselbar Mamuju in terms of overcoming debtors who default are by making efforts to save credit, this is considered very important for banks to avoid the occurrence of bad loans that can affect the soundness of the bank . The recommendation of this research is for creditors and debtors to further enhance their cooperation and compromise with each other so as to establish a more sustainable and effective agreement. In order for the implementation of working capital under the auspices of Bank Sulselbar Mamuju to run smoothly and each party does not suffer losses, the parties fulfill their respective rights and obligations where the debtor must be aware of his obligations.